The outcomes of 25 years of agricultural reforms in Kyrgyzstan; Die Ergebnisse von 25 Jahren landwirtschaftlicher Reformen in Kirgistan - Roman Mogilevskii; Nazgul Abdrazakova; Aida Bolotbekova; Saule Chalbasova; Shoola Dzhumaeva; Kanat Tilekeyev (Leibniz Institute of Agricultural Development in Transition Economies (IAMO), 2017)
Kyrgyz agriculture experienced substantial reform during the 1990s and early 2000s. Subsequently, the pace of reform slowed and at present the government does not appear to have any clear strategy for further development in the sector. Summarizing the outcomes of these reforms, a certain freedom granted to farmers stands out as one of the main achievements and an important reason for the sector's efficiency. Peasant farms are effectively protected from attempts to administratively regulate crop structure or introduce any other types of market distortions. However, an insufficient level of investments is undermining long-term prospects for development in the sector. Supporting large professional players in the sector is one of the key policy priorities of the government. It is however necessary to provide space for these enterprises to emerge on their own. It is additionally important to ensure that any support policies in favor of such players also provide positive spillovers to the small farmers around them, and do not aim at replacing them mechanically. The list of incomplete policy reforms is very long, especially in the area of natural resource management and provision of other essential public goods. The state of pastures and irrigation systems is alarming and requires government support well above its current level. Understanding the key areas for government intervention and focusing interventions on public goods provision should be the key components of a future agricultural development strategy. – – In den 1990er und frühen 2000er Jahren durchlebte die Landwirtschaft in Kirgistan eine Reihe erheblicher Reformen. Das Reformtempo wurde anschließend verringert und zurzeit scheint die Regierung über keine klaren Strategien zur Weiterentwicklung des Sektors zu verfügen. Eine gewisse Entscheidungsfreiheit der Bauern ergibt sich als eines der wichtigsten Ergebnisse der Reformen und wirkt als Treibkraft für die Produktivität des Sektors. Von administrativen Regelungen bezüglich der Struktur der Anbauflächen sowie von der Einführung jeglicher Art Marktbeeinflussung sind Kleinbauernbetriebe meistens nicht betroffen. Allerdings werden langfristige Perspektiven zur Entwicklung des Sektors durch unzureichende Investitionen verhindert. Die großen Agrarbetriebe zu unterstützen, ist eine Hauptpriorität der staatlichen Agrarpolitik. Diesen Betrieben sollte aber genügend Raum geboten werden, um ein eigenständiges Wachstum zu gewährleisten. Zudem ist es wichtig, dass solche Unterstützungsmaßnahmen auch eine positive Wirkung auf die Kleinbetriebe haben und nicht nur zu einer mechanischen Ersetzung führen. Besonders in den Bereichen Management der natürlichen Ressourcen und Bereitstellung öffentlicher Güter ist die Liste der unvollständigen politischen Reformen sehr lang. Der Zustand der Weiden und Bewässerungssysteme erregt Besorgnis und benötigt eine deutlich höhere staatliche Unterstützung als bisher. Die Identifikation von Schlüsselbereichen, für die eine staatliche Intervention nötig ist, sowie eine Schwerpunkverlagerung auf die Bereitstellung von öffentlichen Gütern sollten die Hauptkomponenten einer zukünftigen Strategie zur landwirtschaftlichen Entwicklung darstellen.
urn:nbn:de:gbv:3:2-69129
Keywords: P41; P47; Q15; Q18; 330; farm restructuring; agricultural productivity; irrigation; pasture reform; agricultural policy; Kyrgyzstan; Landwirtschaftliche Umstrukturierung; landwirtschaftliche Produktivität; Bewässerung; Bodenreform; Agrarpolitik; Kirgistan